Exploring hindrances for professionalising South African Private Security Industry: Experiences and recommendations - Mbana, Linda; Khosa, Dorcas; Mofokeng, Jacob Tseko; Maluleke, Witness (Technium Social Sciences Journal, 2021)
The professionalisation of the private security industry (PSI) can be beneficial and costly and these need to be measured against undertaking any professionalisation initiatives, since they can provide some degree of quality control to some businesses working in the field but can also impose hindrances and negative experiences to those wishing to enter the industry. The purpose of this study was to explore the following question: What are the experiences on hindrances to professionalisation of the PSI by Private Security Industry Regulatory Authority [PSiRA] in South Africa? Following a qualitative research approach, this study employed the exploratory research design. The judgemental sampling technique was adopted to select a sample of 40 participants from Gauteng (GP), KwaZulu-Natal (KZN) and Western Cape (WC) provinces. The findings highlighted that the majority of the participants agreed that the professionalisation of the PSI through PSiRA is facing many positive and negative experiences and hindrances, particularly in the private security training space where corruption and criminality are rife. This study recommends that, to overcome the noted hindrances, PSiRA needs to update the training curriculum, empower and train more inspectors and build relationships with industry stakeholders.